1998
DOI: 10.1128/aac.42.8.1980
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M-5, a Novel Cefotaxime-Hydrolyzing β-Lactamase from an Outbreak of Salmonella typhimurium in Latvia

Abstract: At a children’s hospital in Riga, Latvia, isolates identified asSalmonella typhimurium were found to be resistant to expanded-spectrum cephalosporins. Two of the resistant strains were analyzed for the mechanism of cephalosporin resistance. Isoelectric focusing revealed a common β-lactamase with a pI of 8.8. In addition, one of the strains produced a pI 7.6 β-lactamase. A transconjugant producing only the pI 7.6 enzyme was susceptible to expanded-spectrum cephalosporins; therefore, this enzyme was most likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(56 citation statements)
references
References 25 publications
(36 reference statements)
1
51
0
4
Order By: Relevance
“…CTX-M-producing salmonella strains also seem to be widely disseminated in the Baltic countries and Russia. Bradford et al [43] reported an epidemic of ESC-resistant, CTX-M-5-producing S. Typhimurium in Latvia during 1996-1999. The plasmid coding for this ESBL also mediated resistance to a variety of other antibiotic classes.…”
Section: Ctx-m-type β-Lactamasesmentioning
confidence: 98%
“…CTX-M-producing salmonella strains also seem to be widely disseminated in the Baltic countries and Russia. Bradford et al [43] reported an epidemic of ESC-resistant, CTX-M-5-producing S. Typhimurium in Latvia during 1996-1999. The plasmid coding for this ESBL also mediated resistance to a variety of other antibiotic classes.…”
Section: Ctx-m-type β-Lactamasesmentioning
confidence: 98%
“…Resistance to expanded-spectrum ␤-lactam antibiotics in Enterobacteriaceae is often due to the presence of extendedspectrum ␤-lactamases (ESBLs), which are plasmidmediated bacterial enzymes found in enteric Gram-negative organisms [1]. Although reports of ESBLs associated with Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, isolates expressing these enzymes have been identified in Greece, Spain, and Brazil; however, the isolates from Greece came from immigrants from the outbreak areas in Eastern Europe [25,26]. Interestingly, a number of these enzymes have been found among isolates of Salmonella typhimurium [24,28].…”
Section: Extended-spectrum ␤-Lactamasesmentioning
confidence: 95%
“…In addition, the CTX-M-1 and CTX-M-2 enzymes were first detected in single isolates of S. typhimurium [65,66]. In the past few years, large outbreaks of S. typhimurium strains that are resistant to cefotaxime have been reported in eastern Europe [24,28,67]. These strains have all been found to express plasmid-mediated variants of the CTX-M-type ␤-lactamase.…”
Section: ␤-Lactamases In Salmonellamentioning
confidence: 96%
See 1 more Smart Citation